1979
DOI: 10.1159/000212326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Centrophenoxine on the Monovalent Electrolyte Contents of the Large Brain Cortical Cells of Old Rats

Abstract: The effect of centrophenoxine has been studied on the monovalent electrolyte contents of the brain cortical cells of old female Wistar rats by means of energy dispersive x-ray microanalysis. The drug was administered in form of an intraperitoneal injection of 100 mg/kg body weight for 20 days. The treatment decreased the potassium content in both the nucleus and cytoplasm in terms of dry mass fraction, whereas the sodium concentration remained unchanged. The Na+/K+ ratio increased signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, post treatment with CpH resulted in a significant improvement in the cognitive behavior of animals as they escaped only 3.2 trials as compared to Al exposed animals. Zs-Nagy et al [21] also reported that CpH supplementation produced marked improvement in learning, memory, and mental alertness. Similarly, Nandy [22] reported a significant improvement of symptoms such as fatigue, irritability, confusional states, and loss of memory in the geriatric patient treated with CpH.…”
Section: Discussionmentioning
confidence: 95%
“…However, post treatment with CpH resulted in a significant improvement in the cognitive behavior of animals as they escaped only 3.2 trials as compared to Al exposed animals. Zs-Nagy et al [21] also reported that CpH supplementation produced marked improvement in learning, memory, and mental alertness. Similarly, Nandy [22] reported a significant improvement of symptoms such as fatigue, irritability, confusional states, and loss of memory in the geriatric patient treated with CpH.…”
Section: Discussionmentioning
confidence: 95%
“…As explained by the MHA, the age‐dependent decline of the passive potassium permeability in the nerve cells is a key issue in brain aging. CPH treatment for 60 days (80‐100 mg/kg) in old rats reincreased the passive potassium permeability of the neuronal‐cell membrane, that is, it decreased the intracellular potassium content and rehydrated the cytoplasm of brain neurons significantly 62,63. BCE‐001 had the same effect, though a lower dose (60 mg/kg) and a shorter period (3‐4 weeks) of treatment were sufficient to reach the same level as these improvements in rats (unpublished observations).…”
Section: In Vivo Biological Effects Of Cph and Bce‐001mentioning
confidence: 99%